Relationship between Smoking Habit and Nicotine Level with Salivary Flow Rate and pH - Sun nati; Al Furqan; Nuzulul Ismi; Zulfan M Alibasyah; Dewi Saputri (Journal of Indonesian Dental Association, 2025)
Introduction: High nicotine levels from smoking can affect salivary composition and function, which in turn can contribute to oral health problems such as dental caries and periodontal disease. Objective: The purpose of this study was to investigate the relationship between smoking habits and nicotine levels with salivary flow rate and pH in students of the Faculty of Engineering, Universitas Syiah Kuala. Methods: This study was a cross-sectional research design and examined 100 students of the Faculty of Engineering, Syiah Kuala University. Saliva collected by the spitting method. Results: The results of research on students of the Faculty of Engineering, Universitas Syiah Kuala, show that smoking habits and nicotine levels have a significant on the flow rate and pH of saliva in student smokers. Conclusion: There is a significant relationship between smoking habits and nicotine levels in cigarettes, with flow rate and salivary pH in smoking students. The habit of smoking affects the decrease in salivary flow rate and changes in salivary pH, with a moderate to strong strength of relationship.